2015
DOI: 10.1039/c4cc09825k
|View full text |Cite
|
Sign up to set email alerts
|

A dimensionally stable and fast-discharging graphite–silicon composite Li-ion battery anode enabled by electrostatically self-assembled multifunctional polymer-blend coating

Abstract: A high-performance graphite-Si composite anode for Li-ion batteries containing Si nanoparticles (NPs) attached onto graphite microparticles was synthesized by adopting a polymer-blend of poly(diallyl dimethyl-ammonium chloride) and poly(sodium 4-styrenesulfonate). The polymer-blend enabled uniform distribution of Si NPs during synthesis and served as a robust artificial solid-electrolyte interphase that substantially enhanced the cycle stability and rate performance of the composite electrode. The electrode ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…Problematically, the intercalated Si, Li 3.75 Si, swells in volume by about 320% during charging. [15] Zhang et al prepared core-shell structure (Si@C) using silicon nanoparticles (Si-NPs) and emulsion polymerization of acrylonitrile, followed by pyrolysis. [8][9][10][11] Naturally, this is unacceptable for practical and industrial applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Problematically, the intercalated Si, Li 3.75 Si, swells in volume by about 320% during charging. [15] Zhang et al prepared core-shell structure (Si@C) using silicon nanoparticles (Si-NPs) and emulsion polymerization of acrylonitrile, followed by pyrolysis. [8][9][10][11] Naturally, this is unacceptable for practical and industrial applications.…”
mentioning
confidence: 99%
“…Such huge volumetric expansion causes large material stresses, resulting in anode cracking, fracturing, loss of electrical contact (delamination), unstable solid electrolyte interface (SEI) and even catastrophic cell failure. [16] The composite [15] retained A composite anode material synthesized using silicon nanoparticles, micrometer sized graphite particles, and starch-derived amorphous carbon (GCSi) offers scalability and enhanced electrochemical performance when compared to existing graphite anodes. To overcome the capacity limitations of carbon, and the mechanical limitations of silicon, manufacturers have moved into composite materials-with the primary structure consisting of graphitic carbon, with silicon nanoparticles implanted within.…”
mentioning
confidence: 99%
“…Unlike Na(digl) 2 C n , the position of sodium is on the centre of carbon hexagon in graphene sheet. Table 1: Interlayer distance (d int ), average Na/Li−O bond length (d Na-O ), relative volume expansion ratio (r vol ), exfoliation energy (E exf ), and intercalation energy (E int ) of Na(digl)C n and Li(digl) 2 C n (n = 18,20,24,28,32 Table 2: Atomic charge of graphene layer, diglyme molecule (C, H, O), and Na or Li atom in t-GICs Na(digl)C n , Na(digl) 2 C n and Li(digl) 2 Energy and environmental issues become increasingly global, actual and vital to all the nations on the earth. This prompts people to cease from mass consumption of fossil fuels, which are being exhausted and moreover cause greenhouse gas emission, and to create new technologies for utilizing renewable and clean energy sources such as solar and wind power.…”
mentioning
confidence: 99%
“…Silicon is acknowledged as one of the most promising anode candidates owing to its very high theoretical capacity (ca. 3579 mA h g −1 , in the form of Li 3.75 Si), abundance, and moderate potential . Nevertheless, two critical problems must be solved before it can be applied in practice: Firstly, during Li + insertion/extraction the silicon host undergoes volume changes, which causes pulverization and leads to rapid capacity decay upon cycling.…”
Section: Introductionmentioning
confidence: 99%
“…3579 mA hg À1 ,i nt he form of Li 3.75 Si), abundance,a nd moderate potential. [4][5][6][7] Nevertheless,t wo critical problems must be solved before it can be appliedi np ractice:F irstly, during Li + insertion/extractiont he silicon host undergoes volume changes,w hich causes pulverizationa nd leads to rapid capacity decay upon cycling.S econdly, silicon shows poor electronic conductivity because of its semiconductor nature,and this results in poor rate performance. [8][9][10][11] Pioneering works have demonstrated that the construction of nanostructuredp orous silicons with ac onductive wrapping layer is an effective approach to extend cycle life and upgrade rate performance.…”
Section: Introductionmentioning
confidence: 99%